From the mind to the sheet, through the hand. Topicality of freehand sketching in the architectural project. - Chiara Vernizzi (Festival dell'Architettura Magazine, 2022)
In an era in which the digital transaction is increasingly affecting all areas of society, we are aware that this process has already been underway for some time in the context of defining, representing and managing the architectural project. It is necessary to keep the attention on the centrality - not only educational - of the role of freehand drawing, with particular reference to the sketch, in the phase of the initial creative process of the architectural project. The reading of some exemplary drawings produced by leading figures such as Pier Luigi Nervi and Renzo Piano, even if there are obvious differences in approach and architectural outcomes, makes clear the essential role of this moment in which the concept of the project is elaborated and refined in an intimate dialogue. This sees in freehand drawing the still primary and irreplaceable tool for defining the lines and characteristics of the project of the future architecture.